Perancangan Aplikasi Augmented Reality Berbasis Android Sebagai Media Informasi Ruangan Pada Gedung Fakultas Teknik Universitas Riau - Muhammad Sandy Prastyo; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In almost every campus, in introducing the campus environment, they still use the OSPEK (Student Orientation and Campus Introduction) method which is currently considered less effective because it is a waste of time. there is currently no digital media that can provide interactive information about buildings within the Faculty of Engineering, University of Riau. Information about buildings in the Faculty of Engineering, University of Riau requires atechnology that is able to display information interactively and is also more interesting for those who want to get information, both from campus residents themselves and people outside campus who want to get information about campus buildings. In designing and building the applications, of course a method is needed in building the desired application. In this study we used the SDLC (Software Development Life Cycle) method with the waterfallmodel where in this model there are several stages, namely the Analysis Phase, Design Stage, Implementation Stage, Testing, and Maintenance. in using this application we use markers as based tracking in displaying information objects. and it can be concluded that only markers that have been registered can display information about buildings within the University of Riau Faculty of Engineering.Keywords: Augmented Reality, Android, University of Riau, SDLC, waterfall